PERSEPSI IBU HAMIL DALAM PEMERIKSAAN HIV/AIDS DI BANYUMAS - Evicenna Naftuchah Riani; Dewi Ambarwati (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2020)
Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV / AIDS) is still a global problem, including in Indonesia. Where the morbidity and mortality rate have to increase. HIV is a virus that attacks the human immune system, so sufferers are susceptible to various diseases. AIDS is a collection of symptoms and infections resulting from damage to the human immune system caused by HIV infection. Finding of HIV / AIDS cases in Banyumas, has increased cases from year to year. In 2015, there were 251 HIV cases and 125 AIDS cases. Case data in Banyumas is derived from the VCT (Voluntery Counseling and Test) report from general Hospital Prof. Dr. Margono Soekardjo and RSUD Banyumas. The purpose of this study was to look at perceptions of pregnant women towards HIV / AIDS testing. This research uses a qualitative method with a case study. Data collection used in-depth interviews of 8 primary informants and 4 secondary informants as triangulation. The results showed that health care workers in this case midwives did not maintain patient privacy, did not carry out pre and post counseling. HIV / AIDS testing is based on the Health Workers Initiative, and the implementation of integrated examinations in integrated ANC services. There is a gap between theory and implementation in the field. Kata kunci: Persepsi, Ibu hamil, HIV/AIDS. ABSTRAK Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrom (HIV/AIDS) masih menjadi masalah global, termasuk di Indonesia. Dimana angka kesakitan dan kematian yang terus meningkat. HIV merupakan virus yang menyerang sistem kekebalan tubuh manusia, sehingga penderita mudah terkena berbagai penyakit. AIDS merupakan sekumpulan gejala dan infeksi yang timbul karena rusaknya sistem kekebalan tubuh manusia akibat infeksi virus HIV. Penemuan kasus HIV/AIDS di Kabupaten Banyumas, mengalami peningkatan kasus dari tahun ke tahunnya. Tahun 2015, kasus HIV sebanyak 251 dan AIDS sebanyak 125 kasus. Data kasus di Banyumas ini berasal dari laporan VCT (Voluntery Councelling and Test) dari Rumah sakit Prof. Dr. Margono Soekardjo dan RSUD Banyumas. Tujuan dari penelitian ini adalah untuk melihat persepsi ibu hamil terhadap pemeriksaan HIV/AIDS. Penelitian ini menggunakan metode kualitatif dengan studi kasus (case study). Pengumpulan data menggunakan wawancara mendalam (indepth interview) informan primer sebanyak 8 orang dan informan sekunder sebagai triangulasi sebanyak 4 orang. Hasil penelitian didapatkan bahwa petugas pelayanan kesehatan dalam hal ini bidan kurang menjaga privacy pasien, tidak melaksanakan konseling pra dan pasca konseling. Pemeriksaan HIV/AIDS berdasarkan atas inisisati petugas kesehatan, dan pelaksanaan pemeriksaan terintegrasi dalam pelayanan ANC terpadu. Terdapat kesenjangan antara teori dan pelaksanaan di lahan.